A Comparative Simulation Study on the Acoustical Condition of Malaysian Public Secondary Schools’ Classrooms - Chang, Chun Hui; Abdul Wafi, Razali; Nazli, Che Din (Society of Vibration and Acoustics Malaysia, Bangi, 2024)
The establishment of classroom design guidelines is essential in order to provide a conducive setting that promotes optimal teaching and learning outcomes. Most of the learning methods involve hearing and listening which require students to use their auditory skills for speech comprehension. It is vital to design a classroom with optimal acoustic conditions for good speech intelligibility and proper listening quality. However, the importance of classroom acoustics in designing a comfortable learning environment is often neglected. Therefore, this study seeks to i) investigate the acoustic conditions of the existing public-school classrooms and ii) evaluate the effect of several treatment alternatives on acoustic performance through the simulation method. Three (3) classrooms from different public secondary schools were chosen for acoustic evaluations. The existing classrooms’ acoustic parameters, namely reverberation time (RT) and speech transmission index (STI), were initially identified. The impact of acoustic treatments on acoustic performance was further assessed, encompassing variations in ceiling profile configurations and adjustments to surface materials. The findings indicate that the current classrooms' reverberation time (RT) and speech transmission index (STI) did not meet the standard recommendations. Despite the prevailing circumstances, the implementation of acoustic treatments on the ceiling profile and alterations to the surface material yield substantial enhancements in acoustic performance, ultimately leading to the attainment of the required optimal acoustic environment inside the classroom setting.